PERANCANGAN E-LEARNING PADA SMK TAMANSISWA 3 CABANG MATRAMAN JAKARTA - Retno Sari; Herlawati (Jurnal Sistem Informasi, 2014)
Abstract— How to learn is one key factor for menentukkan final result. With a fun way to learn and can be done anywhere, lets add to the spirit of student learning. With the current development of science and technology school can create a website to facilitate students in learning activities. Schools can create e-learning website that allows students to learn independently, which is expected to enhance the spirit of learning. The website can be made with the facilities that support student learning. with these authors make a thesis about the design of e-learning in SMK Tamansiswa 3 Cabang Matraman using PHP and MYSQL. With this website can facilitate students to learn independently, teachers can easily provide the materials and data processing can be done properly and accurately.